Expression of ApoE and Spp1 in the cochlea and auditory cortex of age-related hearing loss mice - Yingxue Yuan; Junhong Zhang; Jingyi Zhao; Xiru Zhang; Zhixin Cao (Brazilian Journal of Otorhinolaryngology)
Objective: Screen for differential proteins in the cochlea of mice associated with Age-Related Hearing Loss (ARHL), analyze and validate the expression of specific differential proteins and genes in the cochlea and auditory cortex of ARHL mice, and preliminarily explore their potential mechanisms of action. Methods: ABR (Auditory Brainstem Response) hearing tests were conducted to select 15-month-old C57BL/6 mice with significantly decreased hearing as the experimental group and 2-month-old mice with normal hearing as the control group. Cochleae were dissected, and unlabeled quantitative proteomics was employed to identify and analyze differentially expressed proteins in the inner ear of the two groups of mice. Key node proteins were selected via the STRING database and Cytoscape analysis. The expression of two selected proteins, ApoE and Spp1, in the cochlea was detected using qRT-PCR, Western blot, and immunofluorescence techniques, and their expression in the auditory cortex of the brain was further explored. Results: Label-free quantitative proteomics identified 115 differentially expressed proteins in the cochlea of 15-month-old ARHL mice compared to 2-month-old hearing-normal mice, including 42 upregulated and 73 downregulated proteins. GO and KEGG enrichment analyses revealed significant enrichment of differentially expressed proteins in functions and signaling pathways associated with neurodegenerative diseases and neurotransmission. Protein-Protein Interaction (PPI) analysis using the STRING database and Cytoscape selection identified ApoE and Spp1 as key hub proteins. Validation via qRT-PCR, Western blot, and immunofluorescence demonstrated that both ApoE and Spp1 were highly expressed in the cochlea and auditory cortex of the ARHL mice compare to 2-month-old hearing-normal mice. Conclusion: ApoE and Spp1 are upregulated in the cochlea of ARHL mice, particularly in spiral ganglion neurons, and in the auditory cortex, suggesting their potential involvement in the pathogenesis and progression of ARHL through the modulation of auditory neural conduction systems. Level of evidence: Level 2.